Risk Factors Affecting Malaria Incidence in Coastal Areas of Indonesia: A Review - Jelin Natalia; Nurul Amalliah (Journal of Health Science and Pharmacy, 2025)
Background: Malaria is an infectious disease caused by Plasmodium parasites that live and multiply in human red blood cells and are transmitted through the bite of infected female Anopheles mosquitoes. Malaria remains a major public health problem worldwide, particularly in tropical and subtropical regions, including Indonesia. Objective: This study aims to identify the dominant factors influencing the incidence of malaria in Indonesia through a comprehensive literature review. Method: This research adopts a qualitative approach using a literature review design. Data were collected and analyzed from previous studies sourced from academic journals available on Google Scholar. The inclusion criteria focused on studies addressing malaria risk factors in the Indonesian context. Results: The review findings indicate that several factors play a significant role in the incidence of malaria in Indonesia. The most frequently reported factors include the level of knowledge about malaria prevention (reported in 8 articles), the presence of mosquito breeding sites (6 articles), the use of mosquito nets (6 articles), and the habit of engaging in outdoor activities at night (5 articles). These factors are consistently associated with higher malaria transmission risks. Conclusion: Efforts to reduce malaria incidence in endemic areas should focus on increasing community awareness and knowledge about malaria prevention, promoting the consistent use of bed nets during nighttime, eliminating mosquito breeding sites through regular environmental sanitation, and minimizing outdoor activities at night when mosquito exposure is high. Additionally, the use of mosquito repellents is recommended as a preventive measure to reduce mosquito bites. Keywords: Malaria, Risk Factors, Coastal Regions, Indonesia